2009
DOI: 10.3168/jds.2008-1806
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Effect of preadjusting test-day yields for stage of pregnancy on variance component estimation in Canadian Ayrshires

Abstract: Preadjustment of phenotypic records is an alternative to accounting for the effect of pregnancy within the genetic evaluation model. Variance components used in the Canadian Test-Day Model may need to be re-estimated after preadjusting for pregnancy. The objective of this study was to assess the effect of preadjusting test-day yields on variance components and estimated breeding values using a random regression test-day model in a random sample of Ayrshire cows. A random sample of 981 Canadian Ayrshire cows fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Similar estimates were obtained with the models with or without the effect of pregnancy, a fact indicating that the lack of inclusion of this effect did not affect the estimates of covariance components. These results agree with Loker et al (2009b), who studied data of milk, fat and protein yield and somatic cell count preadjusted or not for the effect of pregnancy in Canadian Ayrshire cows. The authors found no significant difference in genetic parameters between the two data sets.…”
Section: Resultssupporting
confidence: 82%
“…Similar estimates were obtained with the models with or without the effect of pregnancy, a fact indicating that the lack of inclusion of this effect did not affect the estimates of covariance components. These results agree with Loker et al (2009b), who studied data of milk, fat and protein yield and somatic cell count preadjusted or not for the effect of pregnancy in Canadian Ayrshire cows. The authors found no significant difference in genetic parameters between the two data sets.…”
Section: Resultssupporting
confidence: 82%
“…Jamrozik et al, 1997;Jensen, 2001). TD models are used in many countries (Interbull, 2015), but few studies (Loker et al, 2009) have examined the effects of stage of pregnancy on TD milk yields in variance component estimates. Loker et al (2009) reported that the average heritabilities for daily yields estimated by using a random-regression TD model with TD records that were pre-adjusted for stage of pregnancy were similar to those estimated by using unadjusted records.…”
Section: Introductionmentioning
confidence: 99%
“…(Olori et al, 1997;Penasa et al, 2016). In later stages of gestation, the growth and nutrient requirements of conceptus increases compared with earlier stages (Loker et al, 2009). Furthermore, estrogen levels in maternal blood gradually increase from 3 mo with no meaningful differences in levels between 3 to 5 mo and 5 to 7 mo of pregnancy, followed by a sudden increase thereafter (Parkhie et al, 1966), thereby potentially affecting nutrient partitioning (Olori et al, 1997).…”
Section: Comparison Of Models For Diagnosing Pregnancymentioning
confidence: 97%